2015
DOI: 10.1515/vzoo-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Acanthocephalans Of The Genus Centrorhynchus (Palaeacanthocephala, Centrorhynchydae) From Birds Of Ukraine With The Description Of A New Species

Abstract: The article presents the results of the investigation of material on the genus Centrorhynchus Lühe, 1911 stored in the collection of the Department of Parasitology, Schmalhauzen Institute of Zoology, National Academy of Sciences of Ukraine. Five species: Centrorhynchus aluconis, C. globocaudatus, C. spinosus, C. conspectus and C. polissiensis sp. n. were studied and described. Centrorhynchus polissiensis sp. n., differs from all known species by the complex morphological characters, in particular, by the formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…On the other hand, C. buteonis has been documented not only in Falconiformes and Accipitriformes, but also in owls, especially in the Strix genus (Furmaga, 1957;Yamaguti, 1963;Michálek, 1984;Kritscher, 1985;Sitko 2011;Dimitrova & Dimitrova, 2012;Shirazi et al, 2014). The widest host range, as confi rmed by the above mentioned authors, was observed in C. globocaudatus, primarily infecting diurnal raptors (Sanmartín et al, 2004;Lisitsyna & Greben, 2015). Within our research, a total of 23 helminth species consisting of ten Trematoda species, six Cestoda species, fi ve taxa of the Secernentea class, and one species of Paleacanthocephala were observed for the fi rst time in birds of prey from Slovakia.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…On the other hand, C. buteonis has been documented not only in Falconiformes and Accipitriformes, but also in owls, especially in the Strix genus (Furmaga, 1957;Yamaguti, 1963;Michálek, 1984;Kritscher, 1985;Sitko 2011;Dimitrova & Dimitrova, 2012;Shirazi et al, 2014). The widest host range, as confi rmed by the above mentioned authors, was observed in C. globocaudatus, primarily infecting diurnal raptors (Sanmartín et al, 2004;Lisitsyna & Greben, 2015). Within our research, a total of 23 helminth species consisting of ten Trematoda species, six Cestoda species, fi ve taxa of the Secernentea class, and one species of Paleacanthocephala were observed for the fi rst time in birds of prey from Slovakia.…”
Section: Discussionmentioning
confidence: 78%
“…The majority of literature data on acanthocephalans of birds of prey suggests a rather low host specifi city of individual species of the Centrorhynchus genus. For instance, C. aluconis is considered as an owl parasite in Europe (Kutzer et al, 1982;Kritscher 1985;Ewald & Crompton, 1993;McInnes et al, 1994;Sitko 1994;Dimitrova et al, 1995;Ferrer et al 2004;Dimitrova & Dimitrova 2012;Santoro et al, 2012b;Lisitsyna & Greben, 2015), but it has sometimes been observed also in diurnal raptors (Yamaguti 1963, Illescas Gomez et al 1993Borgsteede et al 2003, Sitko 2011. On the other hand, C. buteonis has been documented not only in Falconiformes and Accipitriformes, but also in owls, especially in the Strix genus (Furmaga, 1957;Yamaguti, 1963;Michálek, 1984;Kritscher, 1985;Sitko 2011;Dimitrova & Dimitrova, 2012;Shirazi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive reports variably document its morphology using only line drawings. Among these, we consider the line drawings in Petrochenko (1950) and Lisitsyna & Greben (2015) to be the most complete and adequately representative. Minor exceptions are noted.…”
Section: Resultsmentioning
confidence: 99%
“…Setting the record straight • Lisitsyna & Greben (2015) stated that the proboscis has a 'maximum width at the anterior part' of males and females and their Fig. 3a shows a posterior proboscis constriction.…”
Section: Discussionmentioning
confidence: 99%
“…Centrorhynchus includes about 90 described species which parasitize a wide variety of avian hosts, being the most speciose acanthocephalan genus parasitic in birds (GOLVAN, 1994). A great number of Centrorhynchus species parasitising diurnal and nocturnal raptors were reported from Italy, Ukraine, Slovakia, USA and Ivory Coast (RICHARDSON & NICKOL, 1995;DIMITROVA & GIBSON, 2005;SANTORO et al, 2010SANTORO et al, , 2012KOMOROVÁ et al, 2015;LISITSYNA & GREBEN, 2015). In South America, there are reports of larval stages (cystacanths) of Centrorhynchus spp.…”
Section: Endoparasitesmentioning
confidence: 99%